Management of Cooking Education to Improve Independence and Motor Skills of Students With Mild Intellectual Disabilities at SLB BC YPLAB Wartawan - Aisy Dzakiyyah Abidin; Ayi Najmul Hidayat (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to examine the management of culinary arts learning in making vegetable soup as a medium for training independence and developing fine motor skills in students with mild intellectual disabilities at the BC YPLAB Wartawan Special School (SLB) in Bandung. Using a qualitative case study approach, this study involved one culinary arts teacher and two students with mild intellectual disabilities. Data collection methods included classroom observation, interviews, and documentation. The results of the study indicate that adaptive and repetitive learning management successfully improved students' independence, strengthened their fine motor skills, and built their self-confidence in practical activities. Evaluation was conducted informally through direct observation, focusing on cognitive, affective, and psychomotor development. Based on these findings, practice-based learning management can be an effective model for special needs education, with an emphasis on vocational skills tailored to the individual needs of students. Keywords: Learning Management, Culinary Arts, Mild Mental Retardation. Abstrak: Penelitian ini bertujuan untuk mengkaji pengelolaan pembelajaran tata boga dalam kegiatan membuat sayur sop sebagai media pelatihan kemandirian dan pengembangan motorik halus siswa tunagrahita ringan di Sekolah Luar Biasa (SLB) BC YPLAB Wartawan, Kota Bandung. Dengan pendekatan kualitatif studi kasus, penelitian ini melibatkan satu guru tata boga dan dua siswa tunagrahita ringan. Metode pengumpulan data dilakukan melalui observasi kelas, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pengelolaan pembelajaran yang adaptif dan berulang berhasil meningkatkan kemandirian siswa, memperkuat keterampilan motorik halus, serta membangun kepercayaan diri siswa dalam aktivitas praktis. Evaluasi dilakukan secara informal melalui observasi langsung, dengan fokus pada perkembangan kognitif, afektif, dan psikomotorik. Berdasarkan temuan ini, pengelolaan pembelajaran yang berbasis praktik langsung dapat menjadi model efektif untuk pendidikan anak berkebutuhan khusus, dengan penekanan pada keterampilan vokasional yang sesuai dengan kebutuhan individu siswa. Kata kunci: pengelolaan pembelajaran, tata boga, tunagrahita ringan.